Entropy production in pp and Pb-Pb collisions at energies available at the CERN Large Hadron Collider - Hanus, Patrick; Reygers, Klaus; Mazeliauskas, Aleksas (Physical review, 2019)
We use experimentally measured identified particle spectra and Hanbury Brown-Twiss radii to determine the entropy per unit rapidity dS/dy produced in √s=7TeV pp and √sNN=2.76TeV Pb-Pb collisions. We find that dS/dy=11335±1188 in 0%-10% Pb-Pb, dS/dy=135.7±17.9 in high-multiplicity pp, and dS/dy=37.8±3.7 in minimum bias pp collisions and compare the corresponding entropy per charged particle (dS/dy)/(dNch/dy) to predictions of statistical models. Finally, we use the quantum chromodynamics kinetic theory pre-equilibrium and viscous hydrodynamics to model entropy production in the collision and reconstruct the average temperature profile at τ0≈1fm/c for high-multiplicity pp and Pb-Pb collisions.
Gesehen am 13.01.2020
Im Titel ist "pp" kursiv geschrieben